2002
DOI: 10.1055/s-2002-35656
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effect of Puerarin on α1A-Adrenoceptor to Increase Glucose Uptake into Cultured C2C12Cells of Mice

Abstract: Effects of puerarin, an active principle contained in the roots of Pueraria lobata (Leguminosae), on the regulation of glucose metabolism in an insulin deficient state were investigated in cultured myoblast C 2 C 12 cells using glucose uptake as indicator. Puerarin enhanced the uptake of radioactive glucose into C 2 C 12 cells in a concentration-dependent manner, which was abolished by prazosin pretreatment. Activation of alpha 1 -adrenoceptors by puerarin was further indicated by the displacement of [ 3H]praz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
5
12
0
Order By: Relevance
“…We assayed the known drug rosiglitazone and 20 compounds extracted from Chinese herbs and successfully identified two non-cytotoxic compounds, puerarin and astragaloside IV. Puerarin has been reported to possess complex pharmacological effects related to diabetes [27], [28], and our results are in agreement with the previous findings. We examined the ability of puerarin and astragaloside IV to modulate glucose uptake and PPARg gene expression.…”
Section: Discussionsupporting
confidence: 94%
“…We assayed the known drug rosiglitazone and 20 compounds extracted from Chinese herbs and successfully identified two non-cytotoxic compounds, puerarin and astragaloside IV. Puerarin has been reported to possess complex pharmacological effects related to diabetes [27], [28], and our results are in agreement with the previous findings. We examined the ability of puerarin and astragaloside IV to modulate glucose uptake and PPARg gene expression.…”
Section: Discussionsupporting
confidence: 94%
“…It contains a unique main isoflavone called puerarin (daidzein 8‐ C ‐glucoside), which shows potent antioxidant and hypolipidemic activities (Chung et al ., ). Many studies have shown various biological activities, such as hypocholesterolemic, antioxidative, hypoglycaemic (Hsu et al ., ; Chung et al ., ) and hypopigmentation effects. Pueraria lobata also contains genistein and daidzein, which are common isoflavones in soybeans (Guerra et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Our study shows that, as rosiglitazone, puerarin dose-dependently potentiate the glucose-uptake of adipocytes, which have been induced insulin resistance by high glucose. Hsu et al reported that puerarin might increase the glucose uptake of C2C12 cell via activating alpha1- adrenoreceptor (Hsu et al, 2002). Our study shows a slow and dissimilar pharmacological action on adipocyte, which implies a new different mechanism with the variation of cell.…”
Section: Discussionmentioning
confidence: 50%